E-Government as New Media of Society Participation in The Development of Sidoarjo, Indonesia - Wahyu Abadi, Totok (2015)
This study discusses the accessibility of e- goverment based public information and its effect on people's participation in evelopment. Respondents in this mixed methods research are 233 users of www.sidoarjokab.go.id. Through a simple random sampling technique, primary data were taken through the distribution of questionnaires were processed and analyzed using path analysis and interactive from Miles-Huberman. This study shows that community participation in development simultaneously and partially influenced by the e-government, quality product information and accessibility. E-Government has a direct influence on the accessibility and public information and indirectly on community participation in development. The new thing in this study is the e –government based public information is a major determinant in improving community participation; e-government are not necessarily able to increase community participation but must be supported by a quality public information. Accessibility of public information, which consists of security and comfort to acquire and convey the aspirations, needs and expectations; openness; availability of the website and the information media; and the ease of the procedure has influenced on community participation in development. The higher the accessibility of e-goverment based public information, the lower public face to face participation